Role of Emotions in Stock Investment Decisions : A Critical Review of the Literature - R., Annapurna; Basri, Savitha (Indian Journal of Finance, 2024)
Purpose : The objective of this study was to use a critical review to examine how emotions arising from different factors, namely, weather, temperature, and number of religious days, influenced investor behavior, especially behaviors that might prevent investors from achieving higher returns. Methodology : Relevant research studies focused on the study objectives were selected from databases that included EBSCO, Web of Science, and Scopus through the PRIMA method. The results of these studies were meticulously analyzed and evaluated. Findings : The review of these studies indicated a mixed effect of emotions on investor behavior that was reflected in stock market movements. External factors such as weather and temperature also affected retail investors’ emotions. ‘Fear’ emotion impacted investor decision-making and caused a herding effect. Investors strive for a positive rather than a negative mood when making investment decisions. Practical Implications : This research provided a comprehensive overview of the studies conducted on emotions arising for different reasons and their relationship to investor behavior, including the dimensions examined and the models employed. The findings can also assist future scholars in locating unexplored gaps in this area. Originality : While numerous researchers have delved into this relation, a comprehensive analysis of various impacts achieved through this review was lacking. The use of the PRISMA model ensured the credibility of this review. We also provided unexplored areas for future research.